Analisis Aset Penghidupan Petani Kentang Varietas Atlantik di Kabupaten Malang: Evi Sriwidayati, Budi Setiawan, Abdul Wahib Muhaimin - Evi Sriwidayati, Budi Setiawan, Abdul Wahib Muhaimin (Pusluhtan, 2023)
Indonesia needs a supply of Atlantic potato varieties for industrial needs, but until now has been met through imports. Atlantic varieties originate from America and can be widely adapted, but when introduced to Indonesia, especially in the East Java region, namely in Poncokusumo and Bumiaji District, Atlantic potato varieties are not able to adapt, so the Atlantic variety potato farming is not sustainable. Currently Malang Regency is developing Atlantic variety potato cultivation in Pujon and Ngantang Districts, a determining factor for the sustainability of Atlantic potato farming according to DFID (2001), including: human capital, natural capital, financial capital, social capital and physical capital. referred to as livelihood assets. The optimal use of livelihood assets is used by farmers to carry out various activities in running Atlantic potato farming. This study in juny until September 2020 aims to analyze the livelihood assets of Atlantic potato farmers in Malang Regency which are scattered in the Pujon and Ngantang Districts with a total sample of 209 respondents and analyzed with asset pentagonals. The results showed the ownership of the livelihood assets of Atlantic potato farmers that social capital got the highest percentage value and financial capital got the lowest percentage value of the five livelihood asset assets analyzed.